Infective endocarditis in patients who have undergone transcatheter aortic valve implantation: a review. (August 2020) - Østergaard, L.; Lauridsen, T. Kiilerich; Iversen, K.; Bundgaard, H.; Søndergaard, L.; Ihlemann, N.; Moser, C.; Fosbøl, E.
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has been approved for the treatment of severe aortic stenosis since 2008 and recent trials have shown that TAVI is at least non-inferior to surgical aortic valve replacement (SAVR) with regards to short-term efficacy and safety in patients across all surgical risk profiles. Prosthetic valve endocarditis of the transcatheter heart valve is a feared complication; data on the risk of infective endocarditis (IE) subsequent to TAVI are now gradually emerging. Objectives: We set forth to conduct a review of the incidence, diagnosis, microbial aetiologies, prevention, outcome and management of TAVI-IE. Sources: From the MEDLINE database we included a total of 12 observational studies and five studies of long-term results from randomized controlled trials. Content: The incidence of TAVI-IE was reported to be between 0.7% and 3.0% per person-year. The most common microbes were reported to be enterococci, Staphylococcus aureus, streptococci and coagulase-negative staphylococci. International guidelines on prevention strategies of IE recommend good sanitary conditions including cutaneous care, good oral hygiene and good care of dialysis catheters. Antibiotic prophylaxis is recommended by guidelines prior to dental procedures in patients with TAVI; however, evidence is sparse. The majority of the patients included in this review with TAVI-IE had an indication for surgical intervention due to IE (50.0% or more); however, only a small subset of the patients underwent surgery (16.4% or less). The in-hospital mortality was around 25%, i.e. of the same order of magnitude as in prosthetic valve IE in general, but varied substantially between studies (from 11% to 64%). Implications: The US Food and Drug Administration's approval of TAVI in patients at low surgical risk may change the characteristics of patients with TAVI, which may influence the incidence, management, and outcome of patients with TAVI-IE.